2020
DOI: 10.1039/c9py01452g
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacture of lightly crosslinked semicrystalline thiol–enes for enhanced mechanical performance

Abstract: Semicrystalline crosslinked thiol–ene networks achieved rapid polymerization kinetics, and mechanical properties substantially improved from the linear thiol–ene thermoplastic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…[ 5–9 ] Introducing alternative crosslinking chemistries to the VAM realm, as well as AM more broadly, is highly desirable as an alternative method to gain access to a wider range of mechanical, thermal, and optical performance. [ 10–14 ] Thiol‐ene‐based polymers are one class of materials that have drawn significant attention owing to their controllable, tunable mechanical properties. [ 15–17 ] This is generally attributed to more uniform molecular networks in thiol‐ene materials, resulting from the step‐growth mechanism of the polymerization reaction.…”
Section: Figurementioning
confidence: 99%
“…[ 5–9 ] Introducing alternative crosslinking chemistries to the VAM realm, as well as AM more broadly, is highly desirable as an alternative method to gain access to a wider range of mechanical, thermal, and optical performance. [ 10–14 ] Thiol‐ene‐based polymers are one class of materials that have drawn significant attention owing to their controllable, tunable mechanical properties. [ 15–17 ] This is generally attributed to more uniform molecular networks in thiol‐ene materials, resulting from the step‐growth mechanism of the polymerization reaction.…”
Section: Figurementioning
confidence: 99%
“…[74][75][76][77] For example, Childress et al used commercially available thiol and alkene monomers with DLP printing to fabricate crosslinked semicrystalline materials with Young's moduli between 40 and 90 MPa while having an elongation at break between 300% and 800%. 78 At the other end of the mechanical properties spectrum, Warner et al demonstrated the use of diallyl diurethane monomers with multifunctional thiols to synthesize materials with Young's moduli between 400 and 2500 MPa, all with elongation at break exceeding 80%. 75 Residual surface thiols and alkenes/alkynes can be used for surface functionalization.…”
Section: Materials Compatible With Vp Polymersmentioning
confidence: 99%
“…This is characteristic of stress-oscillation behaviour observed in numerous polymer systems, however origins of this phenomenon are often disputed. 26,27 A possible explanation is the formation of "voids" in the amorphous regions during elongation which leads to a stress drop and the reorientation of polymer crystallites leading to a stress increase. 28 Remarkably, this behaviour was considerably reduced in samples containing cyclopropane.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%